2020
DOI: 10.1103/physrevb.101.024407
|View full text |Cite
|
Sign up to set email alerts
|

Magnon polarons in the spin Peltier effect

Abstract: We report the observation of anomalous peak structures induced by hybridized magnon-phonon excitation (magnon polarons) in the magnetic field dependence of the spin Peltier effect (SPE) in a Lu2Bi1Fe4Ga1O12 (BiGa:LuIG) with Pt contact. The SPE peaks coincide with magnetic fields tuned to the threshold of magnon-polaron formation, consistent with the previous observation in the spin Seebeck effect. The enhancement of SPE is attributed to the lifetime increase in spin current caused by magnon-phonon hybridizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 47 publications
(98 reference statements)
2
16
0
Order By: Relevance
“…Analogous to polaritons formed from the photon and optical phonon hybridization in semiconductors [9], magnon polarons modify the dispersion of both magnons and phonons and thus affect the thermodynamic and transport properties of the materials. Theoretically proposed over six decades ago [10][11][12][13][14], magnon polarons have not been confirmed until recently in the spin Seebeck effect (SSE) and inelastic neutron scattering (INS) studies on ferrimagnetic insulators including yttrium iron garnet (YIG) [15][16][17][18][19] and Lu 2 BiFe 4 GaO 12 [20]. Unlike INS which requires large single crystal samples, SSE exploits pure spin currents carried by magnons; therefore, it is capable of probing small magnon-polaron anomalies in thin films.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to polaritons formed from the photon and optical phonon hybridization in semiconductors [9], magnon polarons modify the dispersion of both magnons and phonons and thus affect the thermodynamic and transport properties of the materials. Theoretically proposed over six decades ago [10][11][12][13][14], magnon polarons have not been confirmed until recently in the spin Seebeck effect (SSE) and inelastic neutron scattering (INS) studies on ferrimagnetic insulators including yttrium iron garnet (YIG) [15][16][17][18][19] and Lu 2 BiFe 4 GaO 12 [20]. Unlike INS which requires large single crystal samples, SSE exploits pure spin currents carried by magnons; therefore, it is capable of probing small magnon-polaron anomalies in thin films.…”
mentioning
confidence: 99%
“…1(d)] at certain wave vectors k's and energies E's. Just as in YIG [15][16][17][18][19], the AFM magnon polarons are expected to produce anomalies in SSE at specific magnetic fields corresponding to the touching points where the two dispersions are tangential to each other and the overlap regions are maximized in the E-k space.…”
mentioning
confidence: 99%
“…Magnon-polarons could be formed in magnetic-ordered materials due to the strong magnetoelastic coupling between spin waves and lattice vibrations. Recently, a magnon-polarons-induced anomaly has been discovered in the spin Seebeck effect (SSE) of yttrium iron garnet (Y 3 Fe 5 O 12 : YIG) [7,8,11] and the spin Peltier effect of lutetium iron garnet [12]. Besides YIG, Fe 3 O 4 is a ferrimagnetic insulator with strong magnon-phonon coupling [13,14], which makes it a potentially suitable platform to investigate magnon-polarons.…”
Section: Introductionmentioning
confidence: 99%
“…The magnon-phonon polaron induced anomalies in the SSE have been observed also for other magnetic insulators such as antiferromagnetic Cr2O3 [468] and (partially) compensated ferrimagnetic Lu2BiFe4GaO12 [60] and Gd3Ga5O12 [469]. In 2020, Yahiro et al reported that the anomalies show up also in the spin Peltier effect, the reciprocal of the SSE [470]. The formation of magnon-phonon polarons is predicted to affect magnonic spin conductivity and thermal conductivity [467], which await experimental discovery.…”
Section: Magnon-phonon Polaronmentioning
confidence: 84%